Singaporean women : conflicted sexual agents. - Teo, Wen Jia. (2013)
Women from around the world have come a long way since the 1970s. Beyoncé Knowles’s hit single “Run the World (Girls)” is an anthem of female empowerment. The message of the song highlights one thing: girls are the new dominant sex ( Pomerantz, Raby, Stanfaink 2013) The sexual revolution of the 1960-70s has undoubtedly increased women’s call sexual empowerment. Females today are therefore more probable than their female counterparts in the past to view and consider themselves as sexually liberated individuals. (Levy 2005) A cursory look at the current development in the realm of sex was the growing phenomenon of “sexual liberation” among women. (Hooks, 1984) Looking at Singapore, it is a state which strongly upholds the concept of Egalitarianism. As such, women in Singapore are seen to have agency in all aspects of their lives. However, very little research has been done on the aspect of sexual agency. In light of the feminist movement that is seen to enable women to experience “sexual liberation”, this research seeks to explore how young women in Singapore negotiate sexual agency within the interplay of factors (traditionalism, gendered norms and power dynamics) in modern-day intimate heterosexual relationships. Female sexual agency refers to “a young woman’s power to act” referring to women’s feelings of empowerment within the sexual domain, providing the ability and the right to meet their sexual needs (Overlien, 2003)